First, give them a common denominator by multiplying (x-3) and (3-x), which gives you -1(x-3)^2.Then, you have to multiply the first 3 of the numerator with (3-x) and x with (x-3). This will give you x^2-6x+9 over -(x-3)^2, which will simplify to (x-3)^2 over -(x-3)^2.The top and the bottom of the fraction will simplify and give you 1 over -1, which is simply:-1.
-x over 3 can not be simplified.
If 1/x=3/4, then x=1.333.... or 4/3.
If: x/(13-x) = 2/3 Then: x = 5.2
2 x 2 x 3 x 3 over 2 x 2 x 2 x 2 x 3
First, give them a common denominator by multiplying (x-3) and (3-x), which gives you -1(x-3)^2.Then, you have to multiply the first 3 of the numerator with (3-x) and x with (x-3). This will give you x^2-6x+9 over -(x-3)^2, which will simplify to (x-3)^2 over -(x-3)^2.The top and the bottom of the fraction will simplify and give you 1 over -1, which is simply:-1.
-x over 3 can not be simplified.
-2, 3
If 1/x=3/4, then x=1.333.... or 4/3.
If: x/(13-x) = 2/3 Then: x = 5.2
Oh, dude, you're hitting me with some math lingo. So, like, 3 over x is just 3 divided by x. It's like saying you have 3 pieces of candy and you wanna share them with x friends. So, technically correct, but like, who really wants to share candy anyway, am I right?
x/35 = 3/7 => x = 3/7 *35 = 3 * (35/7) = 3*5 = 15
5 over 9 2 x 2 x 5 over 2 x 2 x 3 x 3
x={3, -5} This is if the equation is: 5/(x+2) = x/3. But if you wanted: (5/x) + 2 = x/3, that is different, then x = 3±2*sqrt(6)
x over x is one, so the problem would be 1-2-3/2=-5/3
11x - 9 over 28
-1